The Relationship of Age of Toddlers, Immunization, BBLR, Housing Density and Use of Mosquito Repellent Drugs with the Incidence of ISPA - Dina Dwi Nuryani; Dessy Hermawan; Fitri Eka Sari; Ani Oktasari (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: ISPA is the main cause of high morbidity and mortality rates in early childhood. This disease is caused by many factors, such as characteristics of toddlers and their environment. Objective: This research aims to analyze the relationship between age, immunization, low birth weight (LBW), housing density, and the use of mosquito coils with the incidence of Acute Respiratory Infections (ARI) in toddlers. Methods: This is a quantitative analytical study with a cross-sectional design. The sample consisted of 162 individuals. Data collection was conducted using a questionnaire. Data analysis techniques included the chi-square test and logistic regression. Results: Results showed that 56.2% of toddlers were aged < 3 years; 3.7% had LBW; 33.3% had incomplete immunization; 27.8% lived in crowded housing; 27.8% were exposed to mosquito coils; and ARI incidence was 23.5%. Variables significantly associated with ARI were LBW (p-value: 0.040; OR: 7.176), immunization (p-value: 0.022; OR: 2.543), crowded housing (p-value: 0.004; OR: 3.233), and mosquito coil use (p-value: 0.041; OR: 2.382), while age was not significant (p-value: 0.238). Conclusion: The most dominant variable associated with ARI incidence was immunization (OR: 3.046; CI: 1.360–6.821). Health centers are advised to strengthen ARI prevention programs through increased immunization coverage and continuous monitoring of basic immunization completion. This study provides local epidemiological evidence on combined biological and environmental ARI risk factors at the primary healthcare level, offering a basis for targeted intervention strategies.